ON THE ECOLOGICAL, MORPHOLOGICAL, AND EVOLUTIONARY FEATURES OF BRACHIOPODS LIVING IN MARGINAL AND EXTREME ENVIRONMENTS - Zezina O.N. (My University, 2003)
Both ancient and modern brachiopods provide examples of how adverse environmental conditions (e.g., in marginal areas and submarine caves, on seamount tops, and in the proximity of hydrothermal fields) result in such phenomena as natural selection of small and curytopic forms and developing of stunted and dwarf faunas. The retention of neotenic phenomena (the attainment of sexual maturity and reproductive activity while the lophophore, brachial skeleton, and other morphostructures remain underdeveloped) is accomplished through paedomorphosis and results in such evolutionary consequences as progeny, fetalization, and negative anaboly. This is part of the reason why homeomorphy widely occurs among brachiopods and why some suprageneric brachiopod taxa are polyphyletic.